The effect of four Immeasurables meditations on depressive symptoms: A systematic review and meta-analysis. (March 2020) - Lv, Jing; Liu, Qiuling; Zeng, Xianglong; Oei, Tian P.S.; Liu, Yidan; Xu, Kexin; Sun, Wenxiang; Hou, Hanchao; Liu, Jing
Abstract: The Four Immeasurables Meditations (FIM) intervention have been shown as a promising intervention for reducing depressive symptoms. The current study is a systematic review of FIM intervention effects on depressive symptoms. Among 192 empirical research articles on FIM published before May 2019, 40 independent trials from 35 records measured depressive symptoms. The meta-analysis included 21 randomized controlled trials (RCT; n = 1468) and 16 uncontrolled trials ( n = 376). The results supported overall effectiveness of FIM on depressive symptoms ( d = 0.38 for RCT and d = 0.87 for uncontrolled trials). Moderator analysis indicated the effects differed across protocols, and effects were smaller in RCT using active control groups. No significant differences were observed for participant type, measures, intervention length, or intervention components. Individual studies found no direct association between meditation practice time and effects, and mindfulness and self-compassion were widely supported as mechanisms of change. Current evidence supports FIM as an effective intervention for reducing depressive symptoms, but additional studies with more rigorous designs using active control groups are needed. Further investigation should be encouraged regarding specific protocols and participants, the contribution of meditation practice, and other mechanisms such as positive emotions. Highlights: Four Immeasurables Meditation reduces depressive symptoms in various populations. Large effect sizes were observed in samples with depressive disorders. Effects differ across Four Immeasurables Meditation protocols. Meditation practice and effect are not directly associated. Mindfulness and self-compassion are important mechanisms of change.